Ischemic Stroke Mortality in Type 2 Diabetes in the U.S.: National Trends and Demographic Disparities From 1999 to 2019 - Muhammad Moiz Nasir; Syed Husain Farhan; Hasan Mushahid; Syeda Ayesha Shah; Muhammad Hamza Shuja; Adam Bilal Khan; Syed Hassaan Ali; Syed Ahmed Farhan; Azeem Hassan; Jawad Ahmed; Mohammad Hamza; Javed Iqbal (Endocrinology, Diabetes & Metabolism, 2025)
ABSTRACT Background The pathological changes in the lining of blood vessels associated with diabetes are a well‐established risk factor for stroke, with some studies suggesting a two times increase in risk compared to non‐diabetics. Methods Death certificates from the CDC WONDER (Centers for Disease Control and Prevention Wide‐Ranging OnLine Data for Epidemiologic Research) database were examined from 1999 to 2019 for ischemic stroke‐related mortality in patients with type 2 diabetes mellitus (T2DM). Annual percent change (APC) and age‐adjusted mortality rates (AAMRs) per 100,000 persons were calculated and stratified by year, sex, and race/ethnicity. Results From 1999 to 2019 there were 18,135 deaths from ischemic stroke in patients with T2DM. The AAMR remained relatively constant from 0.31 in 1999 to 0.32 in 2004, gradually declining to 0.14 in 2014 (APC: −6.74), followed by a rapid increase to 0.44 in 2017 (APC: 53.11). Men showed consistently higher AAMR than women in 1999 (AAMR men: 0.34 vs. women: 0.29) and 2019 (AAMR men: 0.55 vs. women: 0.42). When comparing race, African Americans (AA) presented with a consistently higher AAMR in 1999 (AAMR AA: 0.4 vs. white: 0.29) and in 2019 (AAMR AA: 0.62 vs. white:0.44). Notably, a significant escalation in AAMR occurred from 2014 to 2019, affecting both populations; this trend reached its pinnacle in 2019 (2016 AAMR AA: 0.4 vs. white: 0.26) (2019 AAMR AA: 0.62 vs. white: 0.44). Conclusion The findings highlight fluctuating trends in AAMRs with distinct shifts observed after 2014. Noteworthy gender and racial disparities in AAMRs were also evident. The study emphasises the need for ongoing vigilance and focused interventions to address the evolving dynamics of ischaemic stroke‐related mortality in the T2DM population.